REVIEW: PHYTOCHEMICAL CONSTITUENTS AND PHARMACOLOGICAL ACTIVITY OF Strobilanthes crispus - Amin, Azizah (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Strobilanthes crispus (S. crispus), called keji beling leaves, is a plant belonging to the genus Strobilanthes and family Acanthaceae. Keji beling (S.crispus) has been applied by Indonesians to cure some diseases like diabetes and dissolve kidney stones. The aim of this review article is to compile an update on the phytochemical studies and pharmacological activity of S. crispus. A literature review was carried out by searching for articles in the Scopus, PubMed, and Google Scholar data bases between 2014-2024. Studies have shown that the leaves of S. crispus contain flavonoids, phenolics, alkaloids, tannins, terpenoids, phytosterols, and fatty acids. Current pharmacological studies have revealed that the extracts, fractions, or secondary metabolites of S. crispus possess antimicrobial, antioxidant, antidiabetic, anti-urothelial, immunomodulatory, wound healing, cytotoxic, and anti-cancer activities. Although previous studies have provided information about S. crispus, pharmacological and phytochemical data are still limited. Further studies are still necessary to explore the bioactive compounds, toxicity, safety and future development of S.crispus as herbal medicine Keywords: keji beling, Strobilanthes crispus, phytochemical constituent, pharmacological activity